The Poetry Asks for Passing... at School - Esméria de Lourdes Saveli; Regina Janiaki Copes; Solange Salles de Brito (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The article presents the results of a research about the space that the poetry occupies in the school context. It was verified the frequency that the poetical texts are worked, their receptivity among the pupils, the type of activities teachers propose, the difficulties found by them and the conditions offered by the school for the development of these activities. It searched, still, to identify the students' preference in relation to the authors which are presented by the teachers in their classes. The data was gotten by a questionnaire, with half-structuralized questions related to the teachers practicing with the poetical text. This questionnaire was applied, in 2005, in six State schools, in Ponta Grossa, PR. It evidenced that the poetry occupies a shy place in the didactic books that have been the pedagogical support in the Portuguese Language classes and, as a result, it is not much present in the classroom.